2019
DOI: 10.1016/j.ajur.2018.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of testicular torsion presenting with acute abdominal pain in young males

Abstract: ObjectiveTo evaluate the features of testicular torsion presenting with acute abdominal pain and to raise awareness of testicular torsion with specific symptoms.MethodsFrom October 2005 to June 2016, nine patients with testicular torsion who presented with isolated acute abdominal pain rather than scrotal pain as their primary symptom were retrospectively reviewed. Data, including the age of patients, season at admission, initial medical history, external genital examination, emergency ultrasound findings, ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 14 publications
2
18
0
1
Order By: Relevance
“…The delayed presentation of our patients is evident in the mean 4 hours period before presentation. Wang et al also reported a mean period of 4 hours, between the onset of symptoms and presentation to the hospital, for the patients whose testes were salvaged and 37 hours for patients whose testes could not be salvaged [13]. The optimal time frame is less than 6 hours after onset of symptoms [2].…”
Section: Discussionmentioning
confidence: 99%
“…The delayed presentation of our patients is evident in the mean 4 hours period before presentation. Wang et al also reported a mean period of 4 hours, between the onset of symptoms and presentation to the hospital, for the patients whose testes were salvaged and 37 hours for patients whose testes could not be salvaged [13]. The optimal time frame is less than 6 hours after onset of symptoms [2].…”
Section: Discussionmentioning
confidence: 99%
“…Usually, TT can be diagnosed by an external genital examination and color Doppler ultrasound. However, these patients are often initially evaluated by non-urologists who know little about TT; therefore, the diagnosis is delayed or mistaken [5]. TITT may especially be misdiagnosed as acute scrotitis or epididymo-orchitis and traumatic scrotal hematoma [2].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical data including the patient’s age, medical history, scrotal trauma type, mean duration of symptoms before hospitalization, type of pain, external genital examination findings, emergency ultrasound manifestations, operative findings, complications, and follow-up information were collected. Depending upon the testicular blood flow after detorsion, either orchiopexy or orchidectomy was performed [5]; patients with contralateral testes routinely underwent an orchiopexy.…”
Section: Methodsmentioning
confidence: 99%
“…Such atypical presentation is reported in literature, and nearly 12% of children can present only with abdominal pain. [ 3 ] The exact pathophysiology of testicular torsion presenting with abdominal pain is not clear. It could be related to a common innervation between the scrotum (L1 in the anterior part and S2 and S3 in its posterior part), testis, and abdominal organs.…”
mentioning
confidence: 99%
“…The cause could just be mechanical when the twisted spermatic cord or the tensed cremaster muscle pulls and stimulates the peritoneum. [ 3 ] The risk of testicular loss is very high if there is delay in the initial diagnosis of testicular torsion. [ 4 ] The loss of one testis may not significantly impact later paternity or erectile function, but it surely impacts the child's body image and self-confidence.…”
mentioning
confidence: 99%